The effects of graphene oxide nanoparticles on the mechanical and thermal properties of polyurethane/polycaprolactone nanocomposites; a molecular dynamics approach - Shapour Fadaei Heydari; Mohamad Shahgholi; Arash Karimipour; Mehdi Salehi; Seyed Ali Galehdari (Results in Engineering)
Using molecular dynamics simulations using LAMMPS and other tools, this work examined the effect of graphene oxide nanoparticles on the mechanical and thermal properties (TPs) of polyurethane/polycaprolactone nanocomposites. The simulations examined the atomic, MP, and thermodynamic properties of atomic structures while examining and equilibrating them. After 10 ns of equilibration at 300 K and 1 bar, samples were convergent and the simulation parameters were confirmed. The addition of GO-NPs significantly enhanced TPs and MPs, with optimal improvements observed at a 2 % concentration. Specifically, increasing GO-NP content from 0.5 % to 2 % resulted in increases in heat flux from 680.95 to 714.09 W/m2, thermal conductivity from 0.69 to 0.93 W/m·K, and Young's modulus from 5.91 to 6.63 MPa. This is while increasing GO-NP content from 0.5 % to 2 % resulted in decreases in both the mean square displacement and glass transition temperature (Temp) to 0.22 Å2and 318 K, respectively. However, further increasing the GO-NP concentration to 5 % led to a decrease in HF and TC, likely due to nanoparticle agglomeration, which also reduced mechanical strength and increased MSD and Tg. This study underscores the importance of optimizing GO-NP concentration, with 2 % identified as the most effective for enhancing the properties of PU/PCL/GO-NCs.